Pigeon Pea (Cajanus cajan) Seed Meal as Protein Source for Pullets: 2. Response of Pullets to Higher Inclusion Level and Prolonged Feeding of Raw or Processed Pigeon Pea Seed Meal Diets - Amaefule, K.U.; Ojewola, G.S.; Ironkwe, M.C. (International Journal of Poultry Science, 2006)
One hundred and thirty-five nine week-old black Bovan Nera pullets were used to evaluate the response of pullets to higher level and prolonged feeding of raw or processed pigeon pea seed meal (PSM) diets. The experimental design was completely randomized design (CRD) and comprised pullets fed 10% PSM diet during the chick (0-56 days) stage of life that were fed 20% PSM diets. The diets were isoenergetic and isonitrogenous. The seeds were used as raw, boiled for 30 minutes, toasted for 30 minutes or soaked in water for 24 hours. Each treatment (raw, boiled, toasted, soaked or control diet) was replicated three times. Feed intake, weight gain, feed conversion ratio (FCR), daily feed cost, feed cost per kg weight gain and feed cost of raising a pullet to point of lay (POL) were measured. Results showed that prolonged feeding of raw or processed PSM diets to pullets did not significantly affect live weight at POL, daily weight gain, FCR and average mortality while pullets fed raw PSM diet had significantly (P<0.05) lower feed and protein intake than others. Raw PSM diet also significantly reduced daily feed cost and consequently feed cost to POL more than others did. It was concluded that PSM could be a good protein source for pullets from the chick stage to point of lay. PSM could be included as 20% of the grower pullet diet without any adverse effect on performance.